Seroprevalence and Associated Risk Factors of Infectious Bovine Rhinotracheitis (IBR) and Animal Owners’ Knowledge, Attitude and Practice (KAP) Towards the Disease in Selected Districts of East Wollega Zone, Oromia Regional State, Ethiopia - Abdisa Mitiku Danu; Abriham Kebede Deresa; Chala Guyassa Dinagde (Veterinary Medicine and Science)
ABSTRACT Purpose Infectious bovine rhinotracheitis (IBR) is one of the most important diseases affecting production and productivity. Methodology Cross‐sectional study was aimed at to determine the seroprevalence of IBR and associated risk factors, and animal owners’ knowledge, attitude and practice towards the disease from April 2021 to June 2022. Accordingly, a total of 384 serum samples were collected from both crossbreed (70) and local breed (314) cattle from purposively selected districts of East Wollega zone of Western Ethiopia. Competitive enzyme‐linked immunosorbent assay (ELISA) was used for testing glycoprotein antibodies (anti‐gB) for bovine herpes virus‐1 (BoHV‐1) virus in collected serum, and the obtained data were analysed by multiple logistic regressions by using R software 3.62 version. However, questionnaire data were analysed for descriptive statistics by SPSS version 20.0 (IBM. Corp, 2011). Result The total prevalence of IBR in the study area was found to be 70.54% at herd and 80.47% at individual cattle level. The significant association (p <0.05) was found for breed, age, body condition and herd size but not for district and sex as risk factors. The BoHV‐1 virus seropositivity in adult animals increased significantly, with an odds ratio of 1.65 (95% CI 0.705–3.85) compared to young. Local breed cattle were 2.055 times more likely to test positive for IBR with an odds ratio of 0.77 (95% CI 0.23–2.22) compared to crossbreed cattle. The chances of cattle in medium herds testing positive for the BoHV‐1 virus with an odds ratio of (1.78 95% CI 1.303–7.50) are greater than the chances of cattle in smaller herds testing positive. The survey results showed that 70% of animal owners identified IBR as a major challenge in animal production, whereas 35% mentioned long calving intervals. However, 92% of the participants were not informed about the level of knowledge and attitude regarding particular diseases such as IBR. Conclusion This study showed that there is a high prevalence of IBR in cattle in the study area, and that owners have low awareness of the disease. Therefore, it is necessary to develop an immediate control system and conduct additional research on molecular detection to evaluate its effects on reproductive performance.